Influence of perfusion status on central and mixed venous oxygen saturation in septic patients - Goto,Simone Harumi (2017)
Abstract Background and objectives Although there is controversy regarding the role of venous oxygen saturation in the initial resuscitation of septic patients with hypoperfusion these markers are still widely used. This study aimed to evaluate the correlation and concordance between central (SvcO2) and mixed (SvO2) oxygen saturation in septic shock patients with or without hypoperfusion in addition to the impact of these differences in patient conduction. Methods Patients with septic shock were monitored with pulmonary artery catheter and the following subgroups of hypoperfusion were analyzed: 1) lactate > 28 mg.dL-1; 2) base excess ≤ -5 mmol.L-1; 3) venoarterial CO2 gradient > 6 mmHg; 4) SvO2 < 65%; 5) SvcO2 < 70%; 6) lactate > 28 mg.dL-1 and SvO2 < 70%; 7) lactate > 28 mg.dL-1 and SvcO2 < 75%. Results Seventy-seven samples from 24 patients were included. There was only a moderate correlation between SvO2 and SvcO2 (r = 0.72, p = 0.0001) and there was no good concordance between these variables (7.35% bias and 95% concordance limits of -3.0% to 17.7%). Subgroup analysis according to the presence of hypoperfusion showed no differences in concordance between variables. There was discordance regarding clinical management in 13.8% (n = 9) of the cases. Conclusions There is a moderate correlation between SvO2 and SvcO2; however, the concordance between them is inadequate. It was not possible to demonstrate that the presence of hypoperfusion alters the concordance between SvO2 and SvcO2. The use of SvO2 instead of SvcO2 may lead to changes in clinical management in a small but clinically relevant portion of patients.